A Low-Protein Diet Enhances Angiotensin II Production in the Lung of Pregnant Rats but Not Nonpregnant Rats. (19th April 2016) - Gao, Haijun; Tanchico, Daren Tubianosa; Yallampalli, Uma; Yallampalli, Chandrasekhar
Abstract : Pulmonary angiotensin II production is enhanced in pregnant rats fed a low-protein (LP) diet. Here we assessed if LP diet induces elevations in angiotensin II production in nonpregnant rats and whether Ace expression and ACE activity in lungs are increased. Nonpregnant rats were fed a normal (CT) or LP diet for 8, 12, or 17 days and timed pregnant rats fed for 17 days from Day 3 of pregnancy. Plasma angiotensin II, expressions of Ace and Ace2, and activities of these proteins in lungs, kidneys, and plasma were measured. These parameters were compared among nonpregnant rats or between nonpregnant and pregnant rats fed different diets. Major findings are as follows: (1) plasma angiotensin II levels were slightly higher in the LP than CT group on Days 8 and 12 in nonpregnant rats; (2) expression of Ace and Ace2 and abundance and activities of ACE and ACE2 in lungs, kidneys, and plasma of nonpregnant rats were unchanged by LP diet except for minor changes; (3) the abundance and activities of ACE in lungs of pregnant rats fed LP diet were greater than nonpregnant rats, while those of ACE2 were decreased. These results indicate that LP diet-induced increase in pulmonary angiotensin II production depends on pregnancy.